DIGITALIZATION OF THE FINANCIAL ADMINISTRATION SYSTEM TO IMPROVE THE EFFECTIVENESS OF THE FINANCE DEPARTMENT - Edy Sarwono; Hanif Ismail (International Journal of Social Science, 2026)
This study aims to analyze and determine how the implementation of digitalization of the financial administration system can affect the effectiveness of the finance and asset treasury sections of the finance department. It also aims to identify specific areas that indicate inefficiency, potential errors, and bottlenecks in the workflow. It also aims to formulate recommendations for improvements that can be implemented to improve performance. The research method used is a qualitative descriptive method with a case study approach. Data collection was conducted through employee interviews, direct observation of operational workflows, and document analysis related to procedures and financial reports. Based on the research results, it can be concluded that digitalization has had a very positive and significant impact on improving the effectiveness of the finance department. By implementing this digital system, the company not only automates routine and manual tasks but also fundamentally transforms its work methods and control mechanisms. Key findings supporting this conclusion include the existence of work processes that can be combined with previous processes, there are work processes that can be eliminated to increase effectiveness in terms of time and costs, the implementation of an automation-based financial administration system has great potential to improve operational performance and data accuracy. Adopting a designed automation solution can create a more efficient, accurate, and responsive financial administration system to business needs.